Imagery Development in Billie Eilish’s Selected Song - Arsan, Andi Astri; Halim, Abdul; Mustikawati, Yunitari (State University of Makassar, 2025)
This research is entitled “Imagery Development in Billie Eilish’s Selected Songs.” This study aims to analyse the types of imagery in Billie Eilish’s selected songs using theory of Perrine’s (2016) and convey the theme using theory of Mayer’s (1956). The analysis method used qualitative descriptive used refers to the figurative language approach by considering Rozakis’s (1995) theory to explore the kinds of imagery and convey the theme. The research data were obtained from kinds of imagery consisting of visual imagery, auditory imagery, olfactory imagery, gustatory imagery, tactile imagery, kinaesthetic imagery, and organic imagery. The analysis also convey the theme from the different types consisting of repetition, transformation, variation, aesthetics, emotional and cognitive interaction. This research is expected to contribute to the understanding of literature and kinds of imagery also convey the theme. Keywords : Imagery, Theme, Perrine, Mayer, Song, Billie Eilish